An overview on polymeric carbon nitride assisted photocatalytic CO2 reduction: Strategically manoeuvring solar to fuel conversion efficiency. (2nd February 2021) - Kumar, Abhinandan; Raizada, Pankaj; Kumar Thakur, Vijay; Saini, Vipin; Aslam Parwaz Khan, Aftab; Singh, Nahar; Singh, Pardeep
Graphical abstract: Highlights: Fundamentals and influential factors for photocatalytic CO2 conversion. Alluring features of polymeric carbon nitride (g-C3 N4 ) for CO2 reduction. Strategies to enhance photocatalytic efficiency of g-C3 N4 photocatalyst. Extended optical response and charge carrier separation in modified g-C3 N4 . Future research directions on g-C3 N4 assisted CO2 conversion into chemicals. Abstract: Inspired from artificial photosynthesis, photocatalytic CO2 conversion driven by visible light seems to be an effectual tactic to convert CO2 into hydrocarbon fuels like CO, CH4, CH3 OH and HCOOH. Polymeric graphite like carbon nitride (PCN) is a metal-free and reductive type semiconductor photocatalyst with inherent features involving exceptionally well physicochemical firmness and optoelectronic properties. However, the complexity of photoreduction reactions and certain drawbacks associated with pristine PCN demands strategic modulations for its efficient use as sustainable photocatalytic material. The present review involves the comprehensive exploration of photocatalytic CO2 conversion into useful solar fuels starting from fundamentals and important factors influencing photocatalytic CO2 reduction. The review systematically highlights the useful approaches to modulate the major sequential steps of photocatalysis involving visible light absorption and isolation of photocarriers via doping, incorporation of co-catalyst, defect engineering and heterostructure formation. Finally, the review concluded various perspectives and challenges accompanying PCN based photocatalytic CO2 reduction.